2010
DOI: 10.1364/oe.18.015732
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colored nanomaterials using evanescent field-based waveguide sensors

Abstract: We have developed an optical system designed for detecting colored nanomaterials in aqueous solutions, using the concept of evanescent-field-coupled waveguide-mode sensors. In this study, we found that the waveguide modes induced in the sensor are intrinsically sensitive to a change in optical absorption, or a 'change in color'. The system detects less than one gold nanoparticle (diameter: 20 nm) adsorbed per square micrometer. It is also demonstrated that significant signal enhancement due to adsorption of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…6). As shown by Lakshmipriya et al [7], this strategy is more suitable for other novel high performance sensors that have been proposed for bio-recognitions [42][43][44][45]. In conclusion, the present findings collectively contribute to a deeper understanding of the bio-fouling associated with various metal substrates utilized for biosensor engineering.…”
Section: Conclusion and Future Prospectssupporting
confidence: 65%
“…6). As shown by Lakshmipriya et al [7], this strategy is more suitable for other novel high performance sensors that have been proposed for bio-recognitions [42][43][44][45]. In conclusion, the present findings collectively contribute to a deeper understanding of the bio-fouling associated with various metal substrates utilized for biosensor engineering.…”
Section: Conclusion and Future Prospectssupporting
confidence: 65%
“…Using forceps, sterile filter paper discs were transferred onto the surface of the agar plate carefully. The filter paper discs were labeled properly, and each filter paper disc was loaded with different amounts of solutions (20,25,30,35,40, and 45 µL) from the dilutions made. Then, the agar plates were placed in the incubator set at 37°C overnight and monitored on the next day.…”
Section: Disc Diffusion Methods and Determination Of Minimum Inhibitormentioning
confidence: 99%
“…It is widely accepted that metal nanoparticles are harmful to fungi and bacteria [40], and this characteristic allows them to adhere with cell wall of microorganisms, resulting in the destruction and death of the cell. In this study, different concentrations (20,25,30,35,40, and 45 µg) of herbal extracts were tested. The MIC was determined at 45 ug and it was compared with the conjugation with GNPs (Figs.…”
Section: Antimicrobial Activity Of Herbal Extract and Gnp Conjugatementioning
confidence: 99%
See 1 more Smart Citation
“…This surfactant sensor was developed on the basis of waveguide-mode sensor technology. (2)(3)(4)(5)(6) The sensing plate of a waveguide-mode sensor incorporates a thin single-crystalline Si layer and a thin SiO 2 glass layer on a silica glass substrate. It has been reported that the sensor sensitivity can be improved by forming nanopores on the thin SiO 2 layer.…”
Section: Introductionmentioning
confidence: 99%